تأثير العوامل المتعلِّقة بالمصرف على قرار منح الائتمان الصَّغير دراسة ميدانيَّة على المصارف العاملة في السَّاحل السُّوري (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدف هذا البحث إلى دراسة وتحليل مدى تأثير العوامل المتعلِّقة بالمصرف (سيولة المصرف، الاستراتيجيَّة المتَّبعة في المصرف، حصَّة المصرف في السُّوق الائتماني، الإمكانيَّات المادِّيَّة والبشريَّة للمصرف) على قرار منح الائتمان المصرفي الصَّغير للأفراد والمشروعات الصَّغيرة، وذلك في عيِّنة من المصارف العاملة في السَّاحل السُّوري. قامت الباحثة بتوزيع (115) استبياناً على عيِّنة من العاملين في قسم الائتمان في المصارف محل الدِّراسة، وقد بلغ عدد الاستبانات المستردَّة والصَّالحة للتَّحليل والَّتي تمَّ تفريغها (90) استبانة. قامت الباحثة بتحليل البيانات باستخدام برنامج التَّحليل الإحصائي (SPSS 20). وفي نهاية هذا البحث توصَّلت الباحثة إلى مجموعة من الاستنتاجات وأهمّها: يوجد تأثير معنوي لجميع العوامل المتعلِّقة بالمصرف على قرار منح الائتمان الصَّغير، وجاء ترتيب هذه العوامل وفق درجة الأهميَّة والتَّأثير على الشّكل الآتي: الاستراتيجيَّة المتَّبعة في المصرف، سيولة المصرف، الإمكانيَّات المادِّيَّة للمصرف، الإمكانيَّات البشريَّة للمصرف، حصَّة المصرف في السُّوق الائتماني. كما تقدَّمت الباحثة في نهاية البحث بمجموعة من التَّوصيات والَّتي كان أهمُّها: حث الإدارة العليا في المصارف محل الدراسة على صياغة استراتيجيَّة ثابتة وإجراءات محدَّدة تساعد على النَّجاح في عمليَّة اتِّخاذ قرارات منح الائتمان الصَّغير، ضرورة وجود شبكات اتِّصال آليَّة ومتطوِّرة تسمح بتدفُّق المعلومات بين جميع دوائر المصرف وأقسامه بسهولة، توفير المستلزمات المادِّيَّة الضروريَّة لإنجاز الأعمال وتنمية الموارد البشريَّة العاملة في المصارف محل الدراسة. This research was conducted to determine the impact of the factors related to the bank (the liquidity of the bank, the strategy adopted by the bank, the bank's share in the credit market, the material and human resources of the bank) on the decision to grant small bank credit in a sample of banks operating in the Syrian coast. The researcher distributed (115) questionnaires on a sample of the employees in the credit department in the banks under study. The number of questionnaires recovered and valid for the analysis was discharged (90). The researcher analyzed the data using the Statistical Analysis Program (SPSS 20). At the end of this research, the researcher reached a number of conclusions, the most important of which is: There is a significant effect on all factors related to the bank on the decision to grant microcredit, and the order of these factors according to the degree of importance and influence on the following form: the strategy adopted by the bank, liquidity of the bank, the material resources of the bank, the human resources of the bank, The bank's share in the credit market. In addition, the researcher presented the following recommendations: Encouraging senior management in the banks under study to formulate a fixed strategy and specific procedures that will help in the success of the decision making process for the granting of microcredit, the need for automated and sophisticated communication networks that allow the flow of information between all departments and departments easily, Provide the necessary material supplies for the completion of work and development of human resources working in the banks under study.